1991
DOI: 10.1677/joe.0.1290447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin-like growth factor-II on growth hormone release from human somatotrophinoma cells in vitro

Abstract: Insulin-like growth factor-I (IGF-I) and IGF-II receptors have previously been demonstrated on membranes prepared from human somatotrophinomas. IGF-I has been shown to have a variable effect on GH secretion by these tumours in vitro. The effects of purified IGF-II on GH secretion have not been described. We have studied the direct actions of human recombinant IGF-II on GH release from eight somatotrophinomas cultured in vitro. Somatotrophinoma cells were cultured as monolayers at a density of 10(5) cells/0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Third, CSF contains a mix ture of IGF binding proteins, primarily IGF-BP-2 [32], which theoretically could modulate the biological activity of IGF-II. While this latter factor was not controlled in the present experiments, it did not seem to interfere in earlier studies [24,29], Nevertheless, a role for IGF-II in feedback inhibition of GH secretion at a pituitary level is supported by most in vitro studies [20][21][22][23], although it should be noted that a few studies using either normal rat anterior pituitary cells [33] or human somatotrophinoma cells [34] failed to demonstrate an effect of IGF-II. In view of the larger body of evidence implicating IGF-I in GH-negative feed back, both at a pituitary [20][21][22][23]35, 36J and hypothalamic [35,37] level in vitro, as well as in vivo [29], it appears likely that the suppression of spontaneous pulses of GH release which we previously observed in vivo [24] was due primarily to the IGF-1 component of that preparation.…”
Section: Discussionmentioning
confidence: 48%
“…Third, CSF contains a mix ture of IGF binding proteins, primarily IGF-BP-2 [32], which theoretically could modulate the biological activity of IGF-II. While this latter factor was not controlled in the present experiments, it did not seem to interfere in earlier studies [24,29], Nevertheless, a role for IGF-II in feedback inhibition of GH secretion at a pituitary level is supported by most in vitro studies [20][21][22][23], although it should be noted that a few studies using either normal rat anterior pituitary cells [33] or human somatotrophinoma cells [34] failed to demonstrate an effect of IGF-II. In view of the larger body of evidence implicating IGF-I in GH-negative feed back, both at a pituitary [20][21][22][23]35, 36J and hypothalamic [35,37] level in vitro, as well as in vivo [29], it appears likely that the suppression of spontaneous pulses of GH release which we previously observed in vivo [24] was due primarily to the IGF-1 component of that preparation.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that IGF-II inhibits GHRH-stimulated GH release from cultured rat anterior pituitary cells in a dose-dependent manner [6]. In vitro treatment of GH-secreting human pituitary adenomas with IGF-II had a significant inhibitory effect only in 2 out of 8 cases [15]. The presence of specific membrane receptors for IGF-I and IGF-II was demonstrated in primary cultures of human GH-producing pituitary adenomas [5] and in rat pituitary GH-secreting tumour cell lines [29].…”
Section: Discussionmentioning
confidence: 94%